Urgensi Guru PAI dalam Membentengi Akhlak Peserta Didik di Era Disrupsi (Studi Kasus pada Siswa SD Islam Uwais Al Qarni Pekanbaru) - Taupik Prihatin Marpaung; Junaidi Junaidi; Imam Sibaweh; Zulhaini Zulhaini; Bambang Wahyu Susanto (Departement of Mathematics Education, 2023)
In general, what is meant by the Era of Disruption is a period in which massive innovation and change occur. These changes occurred fundamentally, changing various systems and orders to new ways. The characteristic of this era of disruption is that there is a total change that massively changes the behavior of the people, in which these changes tend to be irreversible to normal conditions as before. This research was conducted at the Uwais al Qarni Integrated Islamic Elementary School Pekanbaru which is located at Fajar Ujung Street, Pekanbaru City. This research was conducted for 1 month. The methodology used in this study uses qualitative research methods. The results of this study show the urgency of the existence of Islamic Religious Education Teachers in fortifying the morals of students from the adverse effects of the unstoppable progress of the Disruption Era by making several efforts, including; (1) Instilling the straight values of monotheism, namely monotheism salafussholeh (2) providing an understanding of and the importance of morality, (3) setting a good example for all students (4). strengthening faith by getting closer to Allah Subhanahu Wa Ta'ala, of course, by diligently praying, praying and also diligently reading the Koran, (5) by providing exemplary stories from the time of the Prophet from Islamic figures who had good morals and worthy of imitation and also imitating the morals that the Prophet had applied in his day.